Нові надходження № 6 (червень): інформаційний бюлетень - Прокопенко, Ірина Миколаївна (My University, 2019)
The newsletter contains information on newly arrived publications came to the library of the Scientific and Technical Library in June 2019. Submitted complete bibliographic description of publications. Informed about the number of copies and place finding publications in the structural subdivisions of the library. The material is grouped by sections of the UDC, within the section - in the alphabet of authors or titles of editions The electronic version of the New Benefits newsletter is published on Library site in the "Information activities" section. Monthly from the 25th to the 27th, there are exhibitions of new incomes in the scientific reading room. The bulletin is addressed to scholars, lecturers and students of higher education establishments
Keywords: нові надходження; new incomings